2009
DOI: 10.1093/glycob/cwp013
|View full text |Cite
|
Sign up to set email alerts
|

Capture of heat-killed Mycobacterium bovis bacillus Calmette-Guerin by intelectin-1 deposited on cell surfaces

Abstract: Intelectin is an extracellular animal lectin found in chordata. Although human and mouse intelectin-1 recognize galactofuranosyl residues included in cell walls of various microorganisms, the physiological function of mammalian intelectin had been unclear. In this study, we found that human intelectin-1 was a serum protein and bound to Mycobacterium bovis bacillus Calmette-Guérin (BCG). Human intelectin-1-binding to BCG was inhibited by Ca(2+)-depletion, galactofuranosyl disaccharide, ribose, or xylose, and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 37 publications
(60 reference statements)
4
50
1
Order By: Relevance
“…Angiogenin-4 (encoded by Ang4) has bactericidal activity against several Gram-positive enteric microbes, such as Enterococcus faecalis (38), although E. faecalis was not detectable in our mice. 3 Intelectin-1 (encoded by Itln1) is a host defense lectin that assists phagocytic clearance of microorganisms (43) and is encoded in one of the IBD susceptibility loci (62). This is consistent with our finding that Itln1 was decreased in the colon of Atg7 cKO mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Angiogenin-4 (encoded by Ang4) has bactericidal activity against several Gram-positive enteric microbes, such as Enterococcus faecalis (38), although E. faecalis was not detectable in our mice. 3 Intelectin-1 (encoded by Itln1) is a host defense lectin that assists phagocytic clearance of microorganisms (43) and is encoded in one of the IBD susceptibility loci (62). This is consistent with our finding that Itln1 was decreased in the colon of Atg7 cKO mice.…”
Section: Discussionsupporting
confidence: 89%
“…Next, we performed gene ontology analysis of differentially expressed genes induced by bacterial infection (GO:0042742) or nematode infection (GO:0009624) with a cutoff value of 100. As a result, we found that Itln1 encoding intelectin-1, which is known to be involved in bacterial clearance (43), and Itln2 encoding its homologue intelectin-2 (44) fulfilled these criteria.…”
Section: Expression Of Antimicrobial and Antiparasitic Peptides Was Dmentioning
confidence: 92%
“…6) Additionally, hITLN-1 binds to Mycobacterium bovis bacillus Calmette-Guérin (BCG) and assists in the phagocytic removal of this microorganism. 3) In the present study, we found that recombinant shLFR (hITLN-1) binds tightly to Sepharose (4 Fast Flow [FF], 4B and 6B)-based matrices in a Ca 2+ -dependent manner. This binding property is most likely related to the ability of shLFR, as a host defense lectin, to recognize sepharose (agarobiose)-like, bacteria-specific components that are present on the surface of invading pathogenic microorganisms.…”
mentioning
confidence: 78%
“…1) A soluble form of hLFR (shLFR) is identical to human intelectin-1 (hITLN-1), 2) a galactofuranose-binding protein that plays a role in host defense as lectins to assist in the phagocytic removal of microorganisms. 3) hLFR is expressed as a glycosylphosphatidylinositol (GPI)-anchored protein on human intestinal epithelial cells, Caco-2, 4) while hITLN-1 is expressed as a secretory protein (not as a GPI-anchored protein) in rabbit kidney epithelial cell (RK13) transfectants, despite being present on the cell surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation